HKSCSO: A Novel Enhanced Sand Cat Swarm Optimization Algorithm for UAV Three‐Dimensional Path Planning - Wang, Kang; Zeng, Xin; Xian, Sujie; Li, Zhongxin; Wu, Zhilin (Concurrency and computation, 2025)
ABSTRACT Three‐dimensional path planning for UAV in complex terrains and obstacle‐limited areas is one of the major challenges faced during mission execution, requiring a simple yet effective algorithm. To solve such problems, an improved Sand Cat Swarm Optimization (SCSO) is proposed, addressing the issue where traditional SCSO is prone to getting stuck in local optima. In this improved approach, a nonlinear adjustment mechanism based on a dynamic factor k is introduced to better balance the exploration and exploitation phases. Additionally, the predatory attack strategy of Harris's Hawks was introduced to improve the position update formula during the exploration phase of the SCSO, thus enhancing the algorithm's convergence speed. A new variant of the SCSO, named HKSCSO, is proposed and applied to UAV path planning. Cost functions are introduced to evaluate path length, flight altitude, and angle comprehensively. HKSCSO's performance was tested in three 3D urban environments, showing faster convergence and safer paths compared to SCSO, Harris's Hawks Optimization (HHO), Particle Swarm Optimization (PSO), Seagull Optimization Algorithm (SOA), Whale Optimization Algorithm (WOA), Parrot Optimizer (PO), and Mantis Search Algorithm (MSA). These results indicate HKSCSO's potential as an effective solution for UAV three‐dimensional path planning.